An association selected polymorphisms of XRCC1, OGG1 and MUTYH gene and the level of efficiency oxidative DNA damage repair with a risk of colorectal cancer - Przybylowska, Karolina; Kabzinski, Jacek; Sygut, Andrzej; Dziki, Lukasz; Dziki, Adam; Majsterek, Ireneusz (Mutation research, 2013)
Oxidative damage has been implicated in the pathogenesis of colorectal cancer (CRC). The base excision repair (BER) pathway is the major DNA repair pathway for oxidative DNA damage and genetic variation associated with impaired BER might thus increase a risk of CRC. In this work, we evaluated associations between the repair efficiency of oxidative DNA lesions and single-nucleotide polymorphisms of BER genes: the 194Trp/Arg and the 399Arg/Gln XRCC1, the 326Ser/Cys OGG1 and the 324Gln/His MUTYH and CRC occurrence in a Polish population. These polymorphisms were genotyped in 182 CRC patients and 245 control subjects, using a PCR-RFLP approach. The level of oxidative damage and DNA repair capacity in lymphocytes and CRC tissue samples was evaluated by comet assay using FPG and Nth glycosidases. The 326Ser/Cys OGG1 and the 324Gln/His as well as the 324His/His MUTYH genotypes were found to be associated with an increased CRC risk, while no association was found for the XRCC1 gene polymorphisms. It was also demonstrated the reduced capacity of oxidative damage repair in CRC patients in comparison to healthy controls. Moreover, the decrease efficiency of DNA repair were correlated with the 399Gln/Gln XRCC1 and the 324His/His MUTYH genotypes occurrence in CRC patients. The results obtained in our study indicated an association of OGG1 and MUTYH genes polymorphisms involved in oxidative DNA lesions repair with the risk occurrence of colorectal cancer in Polish patients. It was also found that studied polymorphisms might affect DNA repair capacity suggesting their role in CRC pathogenesis. Finally, we conclude that BER pathway may be an important target for the diagnosis and treatment of colorectal patients.